Ordering of Zn-centered porphyrin and phthalocyanine on TiO2(011): STM studies - Olszowski, Piotr; Zajac, Lukasz; Godlewski, Szymon; Such, Bartosz; Pawlak, Rémy; Hinaut, Antoine; Jöhr, Res; Glatzel, Thilo; Meyer, Ernst; Szymonski, Marek (Beilstein Journal of Nanotechnology, 2017)
Zn(II)phthalocyanine molecules (ZnPc) were thermally deposited on a rutile TiO2(011) surface and on Zn(II)meso-tetraphenylporphyrin (ZnTPP) wetting layers at room temperature and after elevated temperature thermal processing. The molecular homo- and heterostructures were characterized by high-resolution scanning tunneling microscopy (STM) at room temperature and their geometrical arrangement and degree of ordering are compared with the previously studied copper phthalocyanine (CuPc) and ZnTPP heterostructures. It was found that the central metal atom may play some role in ordering and growth of phthalocyanine/ZnTPP heterostructures, causing differences in stability of upright standing ZnPc versus CuPc molecular chains at given thermal annealing conditions.
Keywords: dye-sensitized solar cells; molecular nanostructures; phthalocyanines; porphyrins; rutile surfaces; STM imaging

(untitled) - Capelli, R.; Toffanin, S.; Generali, G.; Usta, H.; Facchetti, A.; Muccini, L. (Nat. Mater., 2010)

(untitled) - Sirringhaus, H. (Adv. Mater., 2014)

(untitled) - O’Regan, B.; Grätzel, M. (Nature, 1991)

(untitled) - Jöhr, R.; Hinaut, A.; Pawlak, R.; Sadeghi, A.; Saha, S.; Goedecker, S.; Such, B.; Szymonski, M.; Meyer, E.; Glatzel, T. (J. Chem. Phys., 2015)

(untitled) - Zajac, L.; Olszowski, P.; Godlewski, S.; Such, B.; Jöhr, R.; Pawlak, R.; Hinaut, A.; Glatzel, T.; Meyer, E.; Szymonski, M. (J. Chem. Phys., 2015)

(untitled) - Sabik, A.; Gołek, F.; Antczak, G. (J. Phys. Chem. C, 2016)

(untitled) - Antczak, G.; Kamiński, W.; Sabik, A.; Zaum, C.; Morgenstern, K. (J. Am. Chem. Soc., 2015)

(untitled) - Auwärter, W.; Écija, D.; Klappenberger, F.; Barth, J. V. (Nat. Chem., 2015)

(untitled) - Wróbel, D.; Boguta, A.; Wójcik, A. (J Phys IV, 2004)

(untitled) - Deng, H.; Zhou, Y.; Mao, H.; Lu, Z. (Synth. Met., 1998)

(untitled) - Diebold, U. (Surf. Sci. Rep., 2003)

(untitled) - Godlewski, S.; Szymonski, M. (Int. J. Mol. Sci., 2013)

(untitled) - Hansen, J. Ø.; Bebensee, R.; Martinez, U.; Porsgaard, S.; Lira, E.; Wei, Y.; Lammich, L.; Li, Z.; Idriss, H.; Besenbacher, F.; Hammer, B.; Wendt, S. (Sci. Rep., 2016)

(untitled) - Li, S.-C.; Chu, L.-N.; Gong, X.-N.; Diebold, U. (Science, 2010)

(untitled) - Addou, R.; Senftle, P. T.; O’Connor, N.; Janik, M. J.; van Duin, A. C. T.; Batzill, M. (ACS Nano, 2014)

(untitled) - Kolmer, M.; Zebari, A. A. A.; Prauzner-Bechcicki, J. S.; Piskorz, W.; Zasada, F.; Godlewski, S.; Such, B.; Sojka, Z.; Szymonski, M. (Angew. Chem., Int. Ed., 2013)

(untitled) - Kolmer, M.; Zuzak, R.; Zebari, A. A. A.; Godlewski, S.; Prauzner-Bechcicki, J. S.; Piskorz, W.; Zasada, F.; Sojka, Z.; Bléger, D.; Hecht, S.; Szymonski, M. (Chem. Commun., 2015)

(untitled) - Godlewski, S.; Tekiel, A.; Prauzner-Bechcicki, J. S.; Budzioch, J.; Gourdon, A.; Szymonski, M. (J. Chem. Phys., 2011)

(untitled) - Godlewski, S.; Tekiel, A.; Prauzner-Bechcicki, J. S.; Budzioch, J.; Szymonski, M. (ChemPhysChem, 2010)

(untitled) - Godlewski, S.; Tekiel, A.; Budzioch, J.; Gourdon, A.; Prauzner-Bechcicki, J. S.; Szymonski, M. (ChemPhysChem, 2009)

(untitled) - Godlewski, S.; Tekiel, A.; Piskorz, W.; Zasada, F.; Prauzner-Bechcicki, J. S.; Sojka, Z.; Szymonski, M. (ACS Nano, 2012)

(untitled) - Tekiel, A.; Godlewski, S.; Budzioch, J.; Szymonski, M. (Nanotechnology, 2008)

(untitled) - Yurtsever, A.; Onosa, J.; Abe, M.; Pang, C. L.; Sugimoto, Y. (J. Phys. Chem. C, 2016)

(untitled) - Dulub, O.; Di Valentin, C.; Selloni, A.; Diebold, U. (Surf. Sci., 2006)

(untitled) - Wagner, S. R.; Huang, B.; Park, C.; Feng, J.; Yoon, M.; Zhang, P. (Phys. Rev. Lett., 2015)

(untitled) - Olszowski, P.; Zajac, Ł.; Godlewski, S.; Such, B.; Jöhr, R.; Glatzel, T.; Meyer, E.; Szymonski, M. (J. Phys. Chem. C, 2015)

(untitled) - Cruickshank, A. C.; Dotzler, C. J.; Din, S.; Heutz, S.; Toney, M. F.; Ryan, M. P. (J. Am. Chem. Soc., 2012)

(untitled) - Lovat, G.; Forrer, D.; Abadia, M.; Dominguez, M.; Casarin, M.; Rogero, C.; Vittadini, A.; Floreano, L. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Torrelles, X.; Cabailh, G.; Lindsay, R.; Bikondoa, O.; Roy, J.; Zegenhagen, J.; Teobaldi, G.; Hofer, W. A.; Thornton, G. (Phys. Rev. Lett., 2008)

(untitled) - Gong, X.-Q.; Khorshidi, N.; Stierle, A.; Vonk, V.; Ellinger, C.; Dosch, H.; Cheng, H.; Selloni, A.; He, Y.; Dulub, O.; Diebold, U. (Surf. Sci., 2009)

(untitled) - Chamberlin, S. E.; Hirschmugl, C. J.; Poon, H. C.; Saldin, D. K. (Surf. Sci., 2009)

(untitled) - Woolcot, T.; Teobaldi, G.; Pang, C. L.; Beglitis, N. S.; Fisher, A. J.; Hofer, W. A.; Thornton, G. (Phys. Rev. Lett., 2012)